Pengaruh Senam Bahu Terhadap Intensitas Nyeri Dan Kemampuan Kemandirian Aktivitas Fungsional Pada Pasien Frozen Shoulder - Wawan Ridwan Mutaqin; Ninik Nur Hidayah (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Frozen Shoulder is only used for a disease that is already well known that is characterized by pain and progressive stiffness in the shoulder that usually lasts 18 months. When it happened and continues to be led to adhesions and joint capsule shrinkage and increased pain. The existence of pain can interfere in the conduct of daily functional activities, both in the area of self-care (self-care), productivity (productivity), and utilization of spare time (leisure). This study aims to determine the effect of exercise on the shoulder pain intensity and ability independence functional activity in patients with frozen shoulder. This study is an experiment with methods of the one group pretest-posttest design. Sampling was done by purposive sampling at dr. Kariadi Hospital. The results showed that there are significant shoulder exercises for pain intensity and ability independence of functional activity in Frozen Shoulder patients at Dr. Kariadi Hospital significant with p = 0.000. Based on age, the majority of respondents are elderly end as many as 13 people (52%), the majority were female gender that 17 people (68%), level of education is high school respondents largely a total of 11 people (44%), and longsuffering majority still lacking 6 months as many as 24 people (96%). The implications of this study that shoulder exercises can be used as an alternative method in occupational therapy intervention in patients with frozen shoulder